Saturday

September 20, 2014

September 20, 2014

Posted by **Taldil** on Tuesday, February 26, 2013 at 6:09am.

- Maths -
**Steve**, Tuesday, February 26, 2013 at 10:16amThis is just a special case of the Bernoulli Equation

y' + p(x) y = q(x) y^n

where q(x) = 1

Make the substitution v = y^(1-n)

This will give you

-v' + (1+1/x)v = 1

Now you can multiply by an integrating factor

e^[∫(1+1/x) dx] = xe^x to get

xe^x v = -e^x (x-1)

and you're almost done

- Maths -
**Taldil**, Wednesday, February 27, 2013 at 6:43amHi..

I'm not sure how to get the final answer

**Answer this Question**

**Related Questions**

Maths - Please help me solve this differential equation : x^3+ ”¼(y+1)”½^(2) dy/...

Engineering Maths - please help solve this differential equation: x^3+(y+1)^2 dy...

Maths - Please help me solve this differential equation: dy/dx+ytanx=y^3”¼sec”½^...

maths - Solve the following differential equation: (1 + x)*(dy/dx) = y where y ...

maths - Solve the following differential equation: (1 + x)*(dy/dx) = y where y ...

maths - how would i solve the differential equation dx/dt=-kx^2 i.e. solve for x...

Maths - Solve the differential equation: d2y/dx2 - 2 dy/dx + y = 3sinhx The ...

Calculus - Solve the differential equation dy/dx = -xe^y and determine the ...

university maths - solve the following differential equation: (x^2+xy)dy=(xy-y^2...

Engineering Maths - Pleas help solve the ffg. differential equation: dy/dx-(1+1/...